2004
DOI: 10.1177/1538192703259249
|View full text |Cite
|
Sign up to set email alerts
|

From Freshman to Graduate: Recruiting and Retaining Minority Students

Abstract: The purpose of this research project was to identify methods to retain minority teacher education candidates and identify curricular and environmental factors that affect recruitment and retention of minority teacher education candidates and student teachers. Because of the low enrollment of minority students in the department in comparison to the number of minority teachers in the state, the researchers desired to ascertain why students choose to remain or leave the department. Focus groups were conducted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…The results revealed that non-Western ethnic minority students earned lower grades than ethnic majority students, confirm ing previous studies reporting that academic careers of ethnic minority students are less successful compared with the academic careers of ethnic majority students (Eimers & Pike, 1997;Hobson-Horton & Owens, 2004;Hofman & Van den Berg, 2003;Jennissen, 2006;Severiens & Wolff, 2008;Swail et al, 2003). The present study focused on one explanation for these differences, namely whether family-study interface issues predict students' academic perfor mance in both ethnic groups in the same way.…”
Section: Explaining Differences Between Ethnic Minority and Ethnic Masupporting
confidence: 92%
See 1 more Smart Citation
“…The results revealed that non-Western ethnic minority students earned lower grades than ethnic majority students, confirm ing previous studies reporting that academic careers of ethnic minority students are less successful compared with the academic careers of ethnic majority students (Eimers & Pike, 1997;Hobson-Horton & Owens, 2004;Hofman & Van den Berg, 2003;Jennissen, 2006;Severiens & Wolff, 2008;Swail et al, 2003). The present study focused on one explanation for these differences, namely whether family-study interface issues predict students' academic perfor mance in both ethnic groups in the same way.…”
Section: Explaining Differences Between Ethnic Minority and Ethnic Masupporting
confidence: 92%
“…Finally, replicating research demonstrating that the academic career of ethnic minority students is less successful than that of ethnic majority students (Eimers & Pike, 1997;Hobson-Horton & Owens, 2004;Hofman & Van den Berg, 2003;Jennissen, 2006;Severiens & Wolff, 2008;Swail et ah, 2003), it is expected that ethnic minority students earn lower grades compared with ethnic majority students.…”
Section: Possible Differences and Similarities Between Ethnic Majoritmentioning
confidence: 95%
“…Research has shown that students from ethnic minority backgrounds on average have lower completion rates in higher education compared to non-minority students (Crul and Wolff 2002;Eimers and Pike 1997;Hobson-Horton and Owens 2004;Jennissen 2006;Just 1999;van den Berg 2002;van den Berg and Hofman 2005). The magnitude of difference in these non-completion rates between ethnic minority and majority students remains unclear.…”
Section: Introductionmentioning
confidence: 97%
“…International data generally show that study careers of ethnic minority students are less successful. They earn less credits in the same amount of time (Hofman and Van den Berg 2003;Severiens and Wolff 2008;Swail et al 2003) and they on average have lower completion rates in higher education compared to non-minority students (Crul and Wolff 2002;Eimers and Pike 1997;Hobson-Horton and Owens 2004;Jennissen 2006;Just 1999; Van den Berg 2002;Van den Berg and Hofman 2005). The present study explores a possible reason for differences in study success.…”
Section: Introductionmentioning
confidence: 99%